Study of interdiffusion in GaInNAs∕GaAs quantum well structure emitting at 1.3μm by eight-band k⋅p method - Dang, Y. X. (2013)
The interdiffusion effect of GaInNAs/GaAs single quantum well sQWd has been investigated with the eight-band k· p method. The as-grown 64-Å Ga0.64In0.36N0.017As0.983 /250-Å GaAs QW is experimentally determined to emit at 1.27 mm in the literature. The compositional profile of the QW after interdiffusion is modeled by an error function distribution. Varying the diffusion length, the effects of interdiffusion on the unstrained band gap, in-plain strain, and confinement profiles are studied. The curve of the ground-state transition (C1-HH1) energy dependence on the interdiffusion length is obtained. Our work shows that the interdiffusion effect on the strain can greatly change the confinement profile of the lighthole (LH), which is confined in the GaAs layer, not in the GaInNAs layer. From the transition energy curve, a blueshift of 51 meV is derived. This interdiffusion mechanism can be utilized in the tuning of the laser operation wavelength.